Acts of Exposure: Reckoning with Representations of HIV and Sexual Identity in Morocco - Anne M. Montgomery; Abderrahim El Habachi (L’Année du Maghreb)
This article presents a hybrid, co-authored exchange between an American academic and scholar of Morocco, Anne Montgomery, and a Moroccan writer and activist, Abderrahim El Habachi. It is a multi-textual work that was produced through an experimental, collaborative method. At the center is an original piece of creative non-fiction, The Story of Naoufel (by El Habachi), which explores the challenges faced by a young gay Moroccan struggling to find care and a sense of belonging after being diagnosed with HIV. The story serves as a springboard for wide-ranging conversations between Anne and Abderrahim on the multiple valences of discrimination, shame, pride, positivity, and activism. This work of methodological bricolage strives to offer concrete lessons for public health programs while simultaneously challenging extant forms of expertise, knowledge production, and the simplistic categories and dichotomies that often frame representations of HIV positivity and sexual identity in Morocco.